As manifestações do mal em Os Verdes Abutres da Colina - Oliveira, Ana Tamires da Silva (2019)
This dissertation develops an analysis of the novel Os Verdes Abutres da Colina from an interpretation of the multiple symbols that constitute evil, focusing on the understanding of its origin and its implications for the development of fictional space and characters located in the center of this problematic, as allies or victims of the evil force that tries to overcome the divine forces and control everyone’s life. The novel, published in 1974, is the result of José Alcides Pinto's commitment to literature since childhood. He soon understood that his vocation was to live with the word in a relationship of extreme obedience, recognizing himself as a mere instrument of the creative impulse. From then on, the mature observation of life and man began to nourish symbols that were incorporated into the alcidian literature. Thus emerged the essential themes that ran through José Alcides Pinto's work from the first to the last text produced: the fear of death (guilt), sin (deviation), the curse (revenge/ punishment) and the demonic. These themes are the threads that weave the narrative around evil and it is the triggering axis of the history of the community of Alto dos Angicos de São Francisco do Estreito. For such discussion and analysis, we draw on the studies of David Roas (2014), Filipe Furtado (1980), Remo Ceserane (2006) and T. Todorov (1992) to consider aspects of alcidian fantastic as a mode of writing; Josep Campbell (2015), Mircea Eliade (1998), Câmara Cascudo (2002), Laura de Melo Sousa (2009) and Carl Jung (2000) as support for analysis of the symbolism contained in the text; Bataille (1987), Freud (2013), Camille Dumoulié (2005) and Lévi-Strauss (1988) in the discussion of eroticism and incestuous relationships between the characters in the novel. We also draw on Paul Ricoeur's research in the Symbolic of Evil (2013) to understand the concepts of sin and stain/ impurity as the strong roots that feed and sustain evil’s conception as having beginning and continuity, but never ending, besides relying on other theorists who deal with the topics covered in this paper.